From empire to empire: The collapse of British America and the rise of imperial republicanism, 1773-1812 - Taylor, TD (2020)
This project examines the idea of an American republican empire from the eve of the Revolution through the Louisiana Purchase. It is built predominantly around the actions of Congress, from its beginnings as an interprovincial summit of British colonies pushing for imperial reform to the federal legislature of an independent nation with oversight of the Republic’s territorial dependencies. Much of it also focusses on the language of empire; descriptions of the Republic as community of polities united under one head and the embrace of the terms ‘colony’ and ‘colonial’ to describe the relationship between the federal government and territorial dependencies. While many historians have written on Thomas Jefferson’s ‘Empire of Liberty’, my aim is to show that the conception of the United States as an empire goes well beyond Jefferson. The title, From Empire to Empire, alludes to the fact that the notion of a US empire has its roots in America’s membership in the British Empire and was built largely on British precedent but with republican innovation. The dissertation is divided into three sections: the first looking at empire and the Revolution; the second at empire in the Early Republic; and the third at empire and the Louisiana Purchase.